Pink-Slipped: What Happened to Women in the Silent Film Industries?, Jane M. Gaines (2018). (1st March 2020) - Phillips, Amelia
Pink-Slipped: What Happened to Women in the Silent Film Industries?, Jane M. Gaines (2018)Urbana, IL: University of Illinois Press, 203 pp., ISBN 978-0-25208-343-3, p/bk, $29.95